Estimation of dry mass of caddisflies Phylloicus elektoros (Trichoptera: Calamoceratidae) in a Central Amazon stream - Martins, Renato Tavares; Melo, Adriano Sanches; Gonçalves, José Francisco Júnior; Hamada, Neusa (Zoologia, 2014)
Aquatic invertebrate biomass estimations are often important in ecological and biological studies. Biomass may be determined by regression models between body and case dimensions and dry mass. Using linear, exponential and power regressions we analyzed the relationship between body and case dimensions and the biomass of Phylloicus elektoros Prather, 2003. Furthermore, we used cross-validation to evaluate the predictions of our models and of the models developed for Phylloicus sp. from southeastern Brazil. We measured four body dimensions (head capsule width, interocular distance, body and pronotum length) of 152 larvae and two case dimensions (width and length) of 45 cases. Case width provided better fit with biomass than case length in all model classes. Body length provided the best biomass prediction. Biomass predictions using models proposed in the literature were 75% lower than the observed values. The power model provided the best fit between body and case dimensions with biomass. However, exponential models also provided good biomass estimates. We observed a close fit between body and case dimensions and biomass, but the predictive power of the models was low (~40%). The predictive power of models proposed in the literature was much worse than those built from local data and thus we do not recommend their use to predict the biomass of organisms from different regions. © 2014 Sociedade Brasileira de Zoologia. All rights reserved.
Keywords: Calamoceratidae; Hexapoda; Phylloicus; Trichoptera